Analysis of the relationship between systemic inflammation and diastolic dysfunction in patients with heart failure and rheumatoid arthritis - A. S. Ankudinov; A. N. Kalyagin (Кардиоваскулярная терапия и профилактика, 2020)
Aim. To study the relationship of the systemic inflammation with the morphological and functional myocardial parameters in patients with heart failure (HF) due to hypertension and coronary artery disease in combination with rheumatoid arthritis (RA).Material and methods. The study included 57 women with NYHA class I-II HF. Patients were divided into two comparable groups: group 1 (n=31) — patients with HF and seropositive RA (Steinbrocker X-ray stage I-III); group 2 (n=26) — HF patients without RA.Results. A comparative analysis of morphological and functional parameters did not reveal significant differences: left ventricular ejection fraction in groups 1 and 2 were 51,06±5,6% and 51,6±6,4%, respectively (p=0,7); the ratio of peak velocity blood flow in early diastole to peak velocity flow in late diastole (E/A) was 0,9±0,1 and 0,8±0,1, respectively (p=0,7). For other echocardiographic parameters, differences were also not detected (p>0,05). Nevertheless, significant regression model was created between the RA activity score (DAS28), rheumatoid factor, and E/A was created: R=0,5; R2 =0,3; F=2,6; p=0,04.Conclusion. As a result of the study, significant direct moderate correlation of the RA activity score (DAS28) with E/A ratio was revealed in the group of patients with HF and RA. The data obtained may indicate an unfavorable prognosis of HF with an increase in RA activity.